Organic ionic plastic crystals: A promising additive for achieving efficient and stable CsPbI2Br perovskite solar cells. (September 2022) - Wang, Chen; Zhang, Boxue; Ma, Xiaohui; Yang, Liqun; Shang, Xueni; Chen, Cong
Abstract: CsPbI2 Br perovskite is a promising candidate for highly efficient photoactive materials. We firstly introduced an organic ionic plastic crystals additive, 1, 1′-Spirobipyrrolidinium hexafluoride (SBP + PF6 − ), to increase the power conversion efficiency and improve the stability by adjusting the crystallization of the CsPbI2 Br perovskite light-absorbing layer and passivating the pinhole defects at the grain boundary. The detailed results reveal that PF6 − molecular anions can fill the vacancy in the X-site and passivate the interface defects. Moreover, SBP + with high conductivity can be used to regulate A-site defects. The results show that the SBP + PF6 − modified device exhibits a champion efficiency of 13.20%, enhanced by 19% than that of the control device. This work proposes not only a straightforward strategy to control the crystallization process in CsPbI2 Br perovskite-based solar cells but also the functionality of organic ionic plastic crystals additive for chemical bonding and defects passivation to improve efficiency and stability. Graphical abstract: We firstly reported an organic ionic plastic crystals additive, 1, 1′-Spirobipyrrolidinium hexafluoride, to improve the efficiency and stability of CsPbI2 Br perovskite solar cells by regulating the crystallization and passivating defects. Image 1 Highlights: First reported use of an organic ionic plastic crystals SBP + PF6 − as additive in CsPbI2 Br perovskite solar cells. SBP + with high conductivity could regulate A-site defects and suppress carrier recombination. PF6 − molecular anions could fill the vacancy in the X-site and passivate the interface defects. The SBP + PF6 − modified device could exhibit an optimized PCE of 13.20% with long-term stability.